(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the effects of group telerehabilitation on pain and disability in patients with chronic low back pain. Methodology: It is a longitudinal retrospective analytical observational study based on the analysis of medical records of patients who underwent three weeks of on-line physical therapy performed in group between september to december 2020. It was evaluated 25 records, considering as the primary outcome the sensation of pain, using Numerical Pain Rating Scale, and as secondary outcomes the disability related to low back pain, evaluated through Roland Morris Disability Questionnaire, and the patient’s perspectives regarding care, before and after the intervention. Results: After data analysis, it was observed a significant reduction in pain intensity (0.007) and disability (0.002) after three weeks of intervention, in addition to positive reports from the patients regarding the experience of telerehabilitation. Conclusion: Group telerehabilitation was effective in improving pain and disability, being satisfactory for patients with chronic low back pain.